2010
DOI: 10.1111/j.1574-6968.2010.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the multiple chaperonins of Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis contains three chaperonin (cpn60) genes homologous to the Escherichia coli groEL gene. One of these (cpn60.1) is required for biofilm formation, but is nonessential, whereas a second (cpn60.2) is essential. Mycobacterium smegmatis is unique among Mycobacteria in having a third chaperonin gene, cpn60.3. The cpn60.1 gene has a gene upstream (cpn10) that is homologous to the gene for the E. coli co-chaperonin GroES. Phylogenetic analysis of the mycobacterial homologues suggests that early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…In addition, GroELs generally require a cochaperonin, GroES, to assist in the folding of target proteins. The genome sequence of M. smegmatis strain mc 2 155 has only one copy of the groES gene, Msmeg_1582 (20,27). This groES gene was cloned into MCS-2 of the pCDFDuet-1 vector (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GroELs generally require a cochaperonin, GroES, to assist in the folding of target proteins. The genome sequence of M. smegmatis strain mc 2 155 has only one copy of the groES gene, Msmeg_1582 (20,27). This groES gene was cloned into MCS-2 of the pCDFDuet-1 vector (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to this, fusion of MimB to an appropriate tag sequence might lead to its high-level soluble expression. Also, the genome sequence of M. smegmatis strain mc 2 155 has two other copies of the groEL gene, Msmeg_0880 and Msmeg_1583, in addition to mimG (Msmeg_1978) (27). These mycobacterial chaperonins might be helpful in the solubilization of MimB.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified two major regulons for heat-shock genes, the HrcA and HspR regulons, which have been demonstrated to control the expression of groE and dnaKJE operons, respectively (Stewart et al 2002). Mtb encodes two copies of groEL genes, groEL1 (cpn60.1) and groEL2 (cpn60.2), and one groES (cpn10) gene, all regulated by HrcA (Rao and Lund 2010). As per the convention, groEL gene that is in operonic arrangement with groES has been termed groEL1, while that that exists separately on the genome has been termed groEL2 (Kong et al 1993;Cole et al 1998).…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
“…Mycobacteria are reported to possess multiple copies of GroELs (23,24). Mycobacterium tuberculosis encodes two copies of groEL, of which groEL1 is arranged in an operon with groES and is dispensable whereas groEL2 is located separately on the genome and is indispensable (25,26).…”
mentioning
confidence: 99%